2014
DOI: 10.3233/jad-130932
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Plasma and Cerebrospinal Fluid as Potential Markers for Alzheimer's Disease

Abstract: The development of Alzheimer's disease (AD) biomarkers remains an unmet challenge, and new approaches that can improve current AD biomarker strategies are needed. Recent reports suggested that microRNA (miRNA) profiling of biological fluids has emerged as a diagnostic tool for several pathologic conditions. In this study, we measured six candidate miRNAs (miR-9, miR-29a, miR-29b, miR-34a, miR-125b, and miR-146a) in plasma and cerebrospinal fluid (CSF) of AD and normal subjects by using quantitative reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(180 citation statements)
references
References 49 publications
11
162
5
2
Order By: Relevance
“…miRNAs are already being used commercially as disease biomarkers in oncology [17]. There is evidence for the use miRNAs as biomarkers in a wide range of diseases including prostate cancer [36], cardiac disease [37], acute kidney injury [38], and Alzheimer's disease [39]. If we could identify miRNAs that could be used as biomarkers for PCOS, the diagnosis and treatment of PCOS would be revolutionized.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are already being used commercially as disease biomarkers in oncology [17]. There is evidence for the use miRNAs as biomarkers in a wide range of diseases including prostate cancer [36], cardiac disease [37], acute kidney injury [38], and Alzheimer's disease [39]. If we could identify miRNAs that could be used as biomarkers for PCOS, the diagnosis and treatment of PCOS would be revolutionized.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of this miRNA correlate with high tau and low Aβ amyloid levels. A second study analysed a selected group of miRNA candidates and observed that miRNAs 34a, 125b and 146a levels were significantly lower in the CSF of AD patients when compared to control cases, while the levels of the miRNAs 29a and 29b were significantly higher [181]. In an independent study low levels of miRNA-146a were also detected in the CSF of AD patients [182].…”
Section: Micrornasmentioning
confidence: 96%
“…However, recent research suggests that miRNAs play an important role in the molecular pathogenesis of both genetic and sporadic AD (Berezin et al, 2014). The expression profile of miRNAs in patients with AD is significantly altered compared to that in controls, and these alterations may play a direct role in regulating the expression of AD-related genes and its subsequent phenotypic manifestations (Kiko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%